(untitled) (Global Journal of Computer Science and Technology, 2016)
The time when someone can do real, publishable mathematics completely without the aid of a computer is coming to a close; the use of computers in mathematical research is both widespread and under-acknowledged. Mathematicians use computers in a number of ways. This paper highlights the importance of mathematics and digital age in today2019;s technological advancement; it also explains the influence of digital age on Mathematics research. Key areas where Information and Communication Technology can be applied to Mathematical research are discussed. To demonstrate the use of computer program on Mathematical analysis, some problems were solved analytically and were also solved using computer programs (Mathlab and Python). These two procedures are compared and it is clearly shown that using computer packages to solve Mathematical problems are more efficient, easier and accurate.